An analysis into the causes of a decline in profitability: a case of Innscor Bread Company - Nhamo, Tsitsidzashe (Midlands State University, 2017)
The study examined the causes of a decline in profitability. The key objective of most businesses is to get a profit. Making profit in business environment usually indicate a healthy business. A favorable effect of business that generates profits is the ability for the company to expand and grow its operations. The study is an analysis of the causes of the decline in Profitability at Innscor Bread Company in Harare. A number of problems in the company performance were experienced which triggered this research.The first chapter is an introduction to the research, showing the background of the study, statement of the problem, research objectives, limitations and delimitation of the study. Chapter two is a review of literature based collectively on opinions of practitioners in the field and explores what other authors have researched and proposed relating to the causes of a decline in profit. Chapter three seeks to-explore methods and techniques that were used in collecting the data and information. The research made use of interviews and questionnaires, which were used to gather data. The data collected in chapter three was analyzed and presented in chapter 4. Chapter 5 concludes the research thereby giving a summary of the findings hence giving recommendations.